Effect of prior beta-blocker use on in-hospital atrial fibrillation development in patients with ST-elevation myocardial infarction - Fatih Kahraman; Akif Arslan; Abdullah Dogan; Yasin Turker; Serdar Guler (Clinical and Experimental Hypertension, 2022)
Background and Aim There are conflicting results about the early administration of beta-blockers (bb) on in-hospital mortality and arrhythmias. Here, we wanted to investigate the effects of chronic bb use on in-hospital Atrial Fibrillation (AF) development in ST-Elevation Myocardial Infarction (STEMI) patients. Materials and Methods A total of 814 consecutive patients with STEMI were included in the study. They were divided into two groups according to whether they are using bb on admission or not. They were followed for AF development in-hospital and predictors of AF were determined by multivariable logistic regression analysis. Results Of the 814 patients, 103 (12.67%) patients were already using bb, while 711 (87.3%) were not. There were no significant differences in the frequency of AF development [3 (%2.9) vs 30 (%4.2), p = .788] between the groups. Multivariable logistic regression analysis showed that left atrial (LA) diameter is the only independent predictor of in-hospital AF development. Conclusions Our study showed that chronic bb use does not have an effect on in-hospital AF development in STEMI patients. Nevertheless, LA diameter was found to be an independent predictor of AF.